FEATURES OF LAND CADASTRE ACCOUNTING: COMPARATIVE ANALYSIS - Жмур, Наталія Володимирівна; Цезар, Анна Романівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to explore the features of land accounting and the role of the land cadastre in land reform, to do the comparative analysis of conduct of cadastre account of Ukraine with the developed countries, for example as Germany, France, USA. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: generalized features of cadastral records of land plots and conditions of obtaining land lease rights. Discussion: the development of land relations in Ukraine is an extremely important process. As land is considered to be the most valuable asset, improving its accounting and control tools is a top priority to ensure a balanced development of the state. Providing information about land on the territory of Ukraine and their distribution by owners and users is vested in the State Land Cadastre, namely its component part - the account of the quantity and quality of land. Land accounting should be considered as a state measure for the accumulation, systematization and analysis of comprehensive information about number, location, economic using of land resources and their natural condition. Data on land counts reflect the actual state of their ussng and are annually reported to all general economic and state bodies of land management. Therefore, the completeness and correctness of land accounting hashuge importance for both land users and authorities, so there is a need to improve the system of accounting for the number of lands, land parcels and especially land use of legal entities formed under different rights. This requires the renewal and improvement of accounting in the state land cadastre in an expanded form.